Correlative Magnetic Resonance Imaging and Histopathology in Small Ruminant Listeria Rhombencephalitis - Precht, Christina; Vermathen, Peter; Henke, Diana; Staudacher, Anne; Lauper, Josiane; Seuberlich, Torsten; Oevermann, Anna; Schweizer-Gorgas, Daniela (Frontiers in Neurology, 2020)
Background: Listeria rhombencephalitis, infection of the brainstem with Listeria monocytogenes, is occurring mainly in humans and farmed ruminants and is associated with high fatality rates. Small ruminants (goats and sheep) are a large animal model due to neuropathological similarities. The purpose of this study was to define MRI features of listeria rhombencephalitis in naturally infected small ruminants and correlate them with histopathology. Secondly, to compare the results with MRI findings reported in humans. Methods: Twenty small ruminants (thirteen sheep, seven goats) with listeria rhombencephalitis were prospectively enrolled, and underwent in vivo MRI of the brain including T2-weighted, FLAIR and T1-weighted sequences pre and post contrast administration and post mortem histopathology. In MRI, lesions were characterized in terms of location, extent, border definition, signal intensity, and contrast enhancement. In histopathology the location, cell type, severity and chronicity of inflammatory infiltrates and signs of vascular damage were recorded. In addition, histopathologic slides were matched to MR images and histopathologic and MRI features were compared. Results: Asymmetric T2-hyperintense lesions in the brainstem were observed in all animals, and corresponded to the location and pattern of inflammatory infiltrates in histopathology. Contrast enhancement in the brainstem was observed in ten animals, and was associated with vessel wall damage and perivascular fibrin accumulation in eight of ten animals. MRI underestimated the extension into rostral brain parts and the involvement of trigeminal ganglia and meninges. Conclusion: Asymmetric T2-hyperintense lesions in the brainstem with or without contrast enhancement can be established as criteria for diagnosis of listeria rhombencephalitis in small ruminants. Brainstem lesions were similar to human listeria rhombencephalitis in terms of signal intensity and location. Different to humans, contrast enhancement was a rare finding and abscessation was not observed.